Effect of Probiotics as Therapeutical and Preventive Modality for Atopic Dermatitis; Lessons from Clinical Trials - SUCIANGTO, WILLIAM; NASRUM, NADA INDIRA RAMADHANI (Nusantara Medical Science Journal, 2024)
Introduction:   Atopic dermatitis is a chronic relapsing inflammatory skin disease that can significantly impact patients' quality of life. Current therapy for atopic dermatitis is corticosteroids, calcineurin inhibitors, and immunosuppressants, but the recurrence of this disease is still reported, and their long-term use is vicious due to their immunosuppressive side effects; the need to discover a new modality that can be used as a therapeutical and preventive modality for atopic dermatitis. Probiotics have been well known for decades due to their various biological activities, including anti-inflammatory and immune-regulatory activity, that have many potential benefits for some skin diseases, including atopic dermatitis. Method:     The method consisted of analyzing and evaluating relevant journal literature published within the past ten years. Result: Several clinical trials have proven the effectiveness of various species of Lactobacilli in improving clinical outcomes for children with atopic dermatitis.  Clinical improvement of atopic dermatitis in children can be achieved not only through the administration of a single probiotic but also by combining different probiotic species. Conclusions:  Based on those studies, probiotics are the potential therapeutical and preventive modality for atopic dermatitis and its primary possible mechanism.